Peptide Hormones in the Insect Midgut - Wu, Kai; Li, Shirong; Wang, Jing; Ni, Yuyang; Huang, Wuren; Liu, Qiuning; Ling, Erjun (Frontiers in Physiology, 2020)
Insects produce many peptide hormones that play important roles in regulating growth, development, immunity, homeostasis, stress, and other processes to maintain normal life. As part of the digestive system, the insect midgut is also affected by hormones secreted from the prothoracic gland, corpus allatum, and various neuronal cells; these hormones regulate the secretion and activity of insects’ digestive enzymes and change their feeding behaviors. In addition, the insect midgut produces certain hormones when it recognizes various components or pathogenic bacteria in ingested foods; concurrently, it regulates other tissues and organs. In addition, intestinal symbiotic bacteria can produce hormones that influence insect signaling pathways to promote host growth and development; this interaction is the result of long-term evolution. In this review, the types, functions, receptors, and mechanisms of hormones working on the insect midgut, as well as hormones produced therein, are reviewed for future reference in biological pest control.